2019
DOI: 10.1155/2019/5179048
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of MicroRNAs as a Biomarker for Hepatocellular Carcinoma: A Meta-Analysis

Abstract: Background Recently, the role of microRNAs (miRNAs) in diagnosing cancer has been attracted increasing attention. However, few miRNAs have been applied in clinical practice. The purpose of this study was to evaluate the diagnostic efficacy of miRNAs for hepatocellular carcinoma (HCC) at early stages clinically. Methods A literature search was carried out using PubMed, Web of Science, and EMBASE databases. We explored the diagnostic value of miRNAs in distinguishing HCC from healthy individuals. The quality ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…For example, miR-26a was identified as a promising biomarker for the diagnosis of early HCC. Even further, the expression levels of miR-221 and miR-101-1 could be used as non-invasive biomarkers for the diagnosis of early HCC from HCV patients [ 33 ]. In the choice of biomarker, in addition to the specificity and accuracy of the test, the method of obtaining the specimen is also a very important consideration.…”
Section: Thyroid Hormone Regulates Non-coding Rnas In Human Liver Cancermentioning
confidence: 99%
“…For example, miR-26a was identified as a promising biomarker for the diagnosis of early HCC. Even further, the expression levels of miR-221 and miR-101-1 could be used as non-invasive biomarkers for the diagnosis of early HCC from HCV patients [ 33 ]. In the choice of biomarker, in addition to the specificity and accuracy of the test, the method of obtaining the specimen is also a very important consideration.…”
Section: Thyroid Hormone Regulates Non-coding Rnas In Human Liver Cancermentioning
confidence: 99%
“…Among miRNAs that were initially found to be promising as diagnostic tools in HCC, miR-21 and miR-122 did not show a different expression in cancer patients in an analysis using RNA sequencing. Differently, miR-101-3p, miR-106b-3p and miR-1246 showed a good diagnostic accuracy, either individually or in combination, when evaluated in HCC patients versus healthy controls or cirrhotic patients [79].…”
Section: Discussionmentioning
confidence: 84%
“…They also suppress the expression of target mRNAs, initiate post‐transcriptional level regulation of target mRNAs, and participate in about 30% of human genome regulation 6 . Several studies have shown that miRNA can be used as an evaluation indicator for diagnosis, staging, and severity of various diseases 11,12 . The miRNAs have been found to be closely related to the pathogenesis of vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have shown that miRNA can be used as an evaluation indicator for diagnosis, staging, and severity of various diseases. 11,12 The miRNAs have been found to be closely re- In this study, high-throughput RNA sequencing was employed to analyze the expression pattern of miRNA between progressive NSV and healthy people. We additionally studied the relationships between abnormal expression of miRNAs and NSV activities.…”
Section: Discussionmentioning
confidence: 99%